Mamíferos de médio e grande porte em uma área de Caatinga de Sergipe e o nicho ecológico de Cerdocyon thous (Linnaeus 1766) - Dias, Douglas de Matos (2014)
There are few studies on the mammalian fauna of the Caatinga s, with most of the first studies focuses on species richness, distribution and foraging ecology. In the state of Sergipe, northeast Brazil, the Caatinga s biome is fragmented and the knowledge of medium and large sized mammals is limited, with most of the information based mainly on inventories. Being so, this work, developed in an area of Caatinga in Sergipe, characterized the community of medium and large sized mammals focused on the richness and habitat use. Besides it evaluated the influence of the seasons on the number of species and records, and the ecological niche of the Cerdocyon thous canid. The study was conducted at the Monumento Natural Grota do Angico (MNGA), an area of 2,138 ha located between the cities of Poço Redondo and Canindé de São Francisco. Samples were taken in three habitats of the MNGA: riparian vegetation, grota and a woody shrubs caatinga s forest. The methodology used included sand plot and camera traps. Samplings were carried between November 2012 and November 2013 in monthly campaigns of 8 days. Ten species of mammals were registered through 571 records, 454 obtained by sand plots and 117 by photos; the order Carnivora being the most representative in the area. Three species were occasionally recorded out of standardized sampling: Lontra longicaudis, Euphractus sexcinctus e Dasypus sp. There were no seasonal difference in the number of records and richness. Kerodon rupestris and small cats differed in terms of habitat use: The first one being more found in the and a grotto, as the second was more found in the riparian vegetation. Overall, the community consists of species habitat generalist. The reduced size of MNGA and the degree of degradation of their environment, caused by the removal of native vegetation for agricultural practice, may have contributed to the low richness observed. Cerdocyon thous showed higher values of frequency of occurrence in the three sampled habitats (Fxy > 0.23) demonstrating its ability to adapt to various habitats. As for the trophic niche, the C. thous diet was classified as omnivorous, with a predominance of arthropods and fruit, vertebrates being consumed on a smaller scale. Even though many items were consumed by the C. thous (N = 32), it focus its diet on a few items, resulting in a low niche breadth value. This specie was constantly active during the night, with few daytime records and was completely inactive between 09:00 to 16:00 h.